Wild vs. Cultivated Zingiber striolatum Diels: Nutritional and Biological Activity Differences - Jing Yang; Yaochen Li; Yuxin He; Hongying He; Xiaoqi Chen; Tingfu Liu; Biao Zhu (Plants, 2023)
Compositional, functional, and nutritional properties are important for the use-value assessments of wild and cultivated edible plants. The aim of this study was to compare the nutritional composition, bioactive compounds, volatile compounds, and potential biological activities of cultivated and wild Zingiber striolatum. Various substances, such as soluble sugars, mineral elements, vitamins, total phenolics, total flavonoids, and volatiles, were measured and analyzed using UV spectrophotometry, ICP-OES, HPLC, and GC-MS methods. The antioxidant capacity of a methanol extract of Z. striolatum, as well as the hypoglycemic abilities of its ethanol and water extracts, were tested. The results showed that the contents of soluble sugar, soluble protein, and total saponin in the cultivated samples were higher, while the wild samples contained higher amounts of K, Na, Se, vitamin C, and total amino acids. The cultivated Z. striolatum also showed a higher antioxidant potential, while the wild Z. striolatum exhibited a better hypoglycemic activity. Thirty-three volatile compounds were identified using GC-MS in two plants, with esters and hydrocarbons being the main volatile compounds. This study demonstrated that both cultivated and wild Z. striolatum have a good nutritional value and biological activity, and can be used as a source of nutritional supplementation or even in medication.